Manajemen Risiko Perencanaan Optimalisasi Pembangunan Jembatan Utama PT Wijaya Karya dengan Metode Failure Mode and Effect Analysis - Yerico Tanu; Purnomo Purnomo (Teknik Industri Universitas Ma Chung, 2021)
PT. Wijaya Karya, a construction company engaged in infrastructure development, is facing the challenge of managing risks in its upcoming project to construct the Main Bridge at Soekarno Hatta Airport, Tangerang, Banten. Poor risk management can result in losses in terms of time, finance, and project outcomes. The study aims to design a risk management system to identify and prioritize risks to be addressed by PT. Wijaya using the Failure Mode and Effect Analysis method. The research results show that the risk of changes in work schedule has the greatest impact on the project and should be handled with the assistance of planning consultant experts. The Construction Department will closely monitor the project results to identify and address any risks that arise. Proper risk management is crucial to ensure the successful completion of the project. This abstract highlights the importance of effective risk management in construction projects, especially in infrastructure development.